Getting it Right: study protocol to determine the diagnostic accuracy of a culturally-specific measure to screen for depression in Aboriginal and/or Torres Strait Islander people. Issue 12 (7th December 2016) - Hackett, Maree L; Farnbach, Sara; Glozier, Nick; Skinner, Timothy; Teixeira-Pinto, Armando; Askew, Deborah; Gee, Graham; Cass, Alan; Brown, Alex
Abstract : Introduction: A freely available, culturally valid depression screening tool is required for use by primary care services across Australia to screen for depression in Aboriginal and/or Torres Strait Islander populations. This is the protocol for a study aiming to determine the validity, sensitivity and specificity of the culturally adapted 9-item Patient Health Questionnaire (aPHQ-9). Methods and analysis: Cross-sectional validation study. A total of 500 people who self-identify as Aboriginal and/or Torres Strait Islander, are ≥18 years of age, attending 1 of 10 primary healthcare services or service events across Australia and able to communicate sufficiently to answer study questions will be recruited. All participants will complete the aPHQ-9 and the criterion standard MINI International Neuropsychiatric Interview (MINI) 6.0.0. The primary outcome is the criterion validity of the aPHQ-9. Process outcomes related to acceptability and feasibility of the aPHQ-9 will be analysed only if the measure is found to be valid. Ethics and dissemination: Lead ethical approval was obtained jointly from the University of Sydney Human Research Ethics Committee (project 2014/361) and the Aboriginal Health and Medical Research Council of New South Wales (project 1044/14). Results will be disseminated via the usual scientific forums, including peer-reviewed publications and presentations at international conferences following presentation to, discussion with and approval by participating primary healthcare service staff and community. Trial registration number: ACTRN12614000705684.